The Multiplicity of Infection of Recombinant Vaccinia Virus Expressing the T7 RNA Polymerase Determines the Rescue Efficiency of Vesicular Stomatitis Virus - Yang, Fan; Tan, Jinlong; Fang, Yongxiang; Chen, Guohua; Zhang, Yongzhi; Hu, Qianqian; Han, Wuweiyi; Liu, Yongsheng; Fu, Baoquan; Jing, Zhizhong; Li, Weike (Frontiers in Microbiology, 2022)
Vesicular stomatitis virus (VSV) has a wide range of cell tropism, making it a prototype of studying the Negative Strand RNA virus (NSRV), including virus-host interactions, vaccine development, et al. Although VSV rescue systems have been progressively optimized throughout time, the T7-based expression system is the most commonly utilized to rescue VSV. However, it remains a significant barrier for many labs. In our study, we found that rescue VSV's efficiency is associated with the various multiplicity of Infection (MOI) of recombinant vaccinia virus expressing the T7 RNA polymerase (vTF-7.3). It works at maximum efficiency while the MOI of vTF-7.3 is 5, which is analyzed by Quantitative PCR, Western Blot, and Flow Cytometry, compared to the lowest rescue level with MOI of 1. Meanwhile, our data also suggest that purification of vTF-7.3 prior to transfection is a prerequisite for VSV rescue. Overall, our study reveals for the first time a precise correlation between vTF-7.3 and rescue efficiency, which may aid in resolving the uncertainties in the quest to build the VSV reverse genetic system.